Use of non-traditional vegetable raw materials in the technology of floury confectionary products for restaurant economy enterprises - Myroshnyk, Yuliya; Dotsenko, Viktor; Sharan, Larisa; Tsyrulnikova, Vita (My University, 2020)
Products of biscuit dough are ones of most popular among floury confectionary products that is conditioned by their taste advantages, and ones of constant elements of food rations. Biscuit semi-products are a base of such confectionary products as tarts, fancy cakes, cookies. It is expedient to use supplements of non-traditional raw materials that can not only influence the technological process and quality of ready products, but also enrich them with biologically active substances as additional components of floury confectionary products. The most promising raw material for enriching products of this group is vegetable powders, because fresh products are seasonal and don’t regularly provide the food ration of the population with biologically active substances. The article considers a possibility of using snowball, ashberry and buckthorn powders for making biscuit semi-products. The aim of the work was to study the expedience and technological possibility of using vegetable raw materials in the biscuit semi-prod- uct technology. The chemical composition of chosen powders was studied. The influence of vegetable powder on the quality and quantity of cellulose, structural-mechanical and physical properties of dough was established. The expedience of using surface-active substanc- es in the biscuit semi-product technology for improving the quality of ready products was substantiated.
Keywords: floury confectionary products; biscuit semi-product; vegetable powders; non-traditional vegetable raw materials; борошняні кондитерські вироби; бісквітний напівфабрикат; рослинні порошки; нетрадиційна рослинна сировина; кафедра готельно-ресторанної справи